Content Validity Of English Semester Test Designed by English Teacher at Mtss Bustanul Ulum Kota Padang - Aprilia, Disa (EduCurio: Education Curiosity, 2023)
Validity analysis is very necessary to determine the quality of the questions created by the teacher. However, the phenomenon found was that a number of test items were still found that did not match the indicators in making the test items. Therefore, this research aims to describe the validity of the content of the 7th grade English test questions for the even semester of the 2022/2023 academic year at MTsS Bustanul Ulum, Padang City. This type of research is descriptive qualitative. The data source for this research is a blueprint for even semester 7th grade English tests and questions. This test consists of 40 multiple choice questions. To obtain data, in this study researchers used an instrument in the form of a checklist document. In this study, researchers used data content analysis techniques. There are 5 steps in data analysis used by researchers, namely first, preparing the data for analysis. Second, read all the data that will be used. Third, start analyzing the data using the coding process. Fourth, start processing the data from the coding process. Fifth, make an interpretation of the data processing that has been carried out. The results of this research show that the multiple choice questions created by the teacher contained 27 valid questions and 3 invalid questions. Valid questions consist of questions number 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 , 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 39 and 40. Invalid questions consist of questions number 36, 37 and 38.